Implementasi Kurikulum Materi Al-Qur’an di Sekolah Dasar Islam (SDIT) Bani Saleh Cikembar - Emi Tresnawati; Siti Qomariyah; Aat Yuniawati; Lussi Hermawati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to find out the implementation of the Qur'an curriculum in Islamic elementary schools, focusing on planning, execution, evaluation, and supporting or inhibiting factors. A qualitative descriptive method with a case study approach was applied through interviews, observations, and document analysis. The findings show that the Qur'an curriculum is implemented using Islamic values-based approaches, involving reading, memorizing, and understanding the Qur'an. Teachers utilize interactive and contextual methods to enhance student engagement. Key supporting factors include teacher competence and learning facilities, while challenges consist of limited time allocation and varying student abilities. The study recommends periodic teacher training and innovative learning strategies to optimize Qur'an learning outcomes